Weed and Pest Control (IntechOpen, 2021)
This book covers alternative insect control strategies, such as the allelopathy phenomenon, tactics in integrated pest management of opportunistic generalist insect species, biological control of root pathogens, insect pest control by polyculture strategy, application of several integrated pest management programs, irrigation tactics and soil physical processes, and carbon stocks to manage weeds.